Öffentliche Institutionen als weiße Räume?: Rassismusreproduktion durch ethnisierende Kategorisierungen in einem schweizerischen Sozialamt - Wagner, Constantin (transcript, 2017)
How does the perceived »ethnic affiliation« change the treatment of clients in public institutions? About the whiteness of social workers and its consequences.